Experimental studies of hysteresis behavior of partial cavitation around NACA0015 hydrofoil. (1st December 2020) - Seyfi, Siamak; Nouri, Nowrouz Mohammad
Abstract: Partial cavitation is one of the main cavitation regimes occurring in hydrofoil sections. In this study, the effect of gradually increasing and decreasing the angle of attack (α) on partial cavitation of hydrofoils, has been investigated. A new hysteresis phenomenon is observed in a difference of partial cavity length in increasing and decreasing of α. The angle of attack (α) changed from zero to twenty, then from twenty to zero by a step of two degrees at each level. In each α, twelve pictures are taken and optimized using image-processing techniques. Then the partial cavity length is defined as the average value of twelve obtained data. Comparing the results in zero to twenty range by twenty to zero range, hysteresis in partial cavity length is observed. To investigate the repeatability of the results, this procedure is repeated in nine different cavitation numbers varying between 2.35 and 1.72. The same phenomenon is observed in all experiments. Highlights: There is a difference in partial cavity length at the same α in increasing and decreasing half-cycles, defined as hysteresis. Hysteresis phenomenon always occurs in partial cavitation formation, but its value has an oscillatory behavior. The statistical averaged value is representative of the flow condition due to the unsteady behavior of partial cavitation. Obtained results showed that the maximum difference in length is between α = 12° and 16° for all flow conditions.